PENGEMBANGAN PEMASARAN ES TEH D’MIRA DI KOTA BLORA DALAM ANALISIS SWOT - Andika Dimas Pramuditya; Yulyar Kartika Wijayanti; Nekky Rahmiyati (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
D’Mira developed an ice tea business strategy using SWOT and BMC analysis as a reference to identify strengths, weaknesses, opportunities and threats. Also learn in detail about strategic management tools to define and communicate business ideas or concepts quickly and easily. The aim of this final task is to identify the factors that affect thecompetitiveness of D'Mira ice cream and to find out business development strategies that canbe applied in expanding market share as well as selling competitive products.The internal factor that D’Mira’s ice tea has is that this ice is the raw material of a quality product, refreshing and suitable for drinking in a variety of weather with a distinctiveflavor, served with a wide variety of flavors, and the cost of producing ice tea is relatively low.D’mira’s development strategy is to promote products that have to be done frequently to reacha wider market share, as well as record significant financials to identify relevant losses or gains.The results in the table above indicate that the primary strategy generated is the SO strategy with the highest rating of 4.26 in position 1, i.e. using power to harness and harnessthe greatest opportunity. Based on the results and discussions that have been conducted, it canbe concluded that the development of D’Mira’s ice tea strategy carries out the development strategy by paying attention to strengths and opportunities so that it is sufficiently responsiveor responsive to the existence of opportunities and threats that occur. Keywords : Business Development, Business Strategy, SWOT